THE EFFECTIVENESS OF AROMATHERAPY RELAXATION TECHNIQUES AND SLOW STROKE BACK MASSAGE STIMULATION ON CHANGES IN PAIN INTENSITY IN POST-HYDRONEPHROSIS SURGERY PATIENTS AT AMIRA GENERAL HOSPITAL IN 2024 - Basahudin, Deri Afrido; Purnama, Agus; Koto, Yeni (Nurse and Health: Jurnal Keperawatan, 2025)
Background: Post-hydronephrosis surgery patients may experience pain. The physical impacts of pain include rapid breathing, increased heart rate, elevated blood pressure, increased stress hormones, delayed healing, and decreased immune function. Pain reduction can be achieved through pharmacological and non-pharmacological approaches. One non-pharmacological method includes aromatherapy relaxation therapy, SSBM stimulation, and a combination of both aromatherapy relaxation and SSBM stimulation. Objectives: To identify the effectiveness of aromatherapy relaxation techniques and slow stroke back massage stimulation on changes in pain intensity among post-hydronephrosis surgery patients at Amira General Hospital Methods: This study utilized a quantitative research approach with a quasi-experimental design, specifically employing a pretest-posttest design with three intervention groups. The population consisted of post-hydronephrosis surgery patients at Amira General Hospital. The sample involved 21 respondents, divided into three groups: aromatherapy relaxation therapy (7 respondents), SSBM stimulation (7 respondents), and a combination of aromatherapy relaxation and SSBM stimulation (7 respondents). The sampling technique used was purposive sampling. The research instrument used for data collection was an observation sheet. Data analysis was conducted using dependent t-test and independent t-test. Results: The study found that changes in pain intensity before and after intervention in post-hydronephrosis surgery patients showed the following p-values: aromatherapy relaxation therapy p = 0.3711, SSBM stimulation p = 0.001, combination therapy (aromatherapy relaxation and SSBM stimulation) p = 0.017, and combination therapy p < 0.001. Based on the independent t-test results, p < 0.05 indicated a significant difference in pain intensity changes between aromatherapy relaxation, SSBM stimulation, and their combination in post-hydronephrosis surgery patients at Amira General Hospital. Conclusion: Slow Stroke Back Massage (SSBM) stimulation and the combination therapy (Aromatherapy + SSBM) demonstrated a significant effect on reducing pain intensity in post-hydronephrosis surgery patients. However, aromatherapy relaxation alone did not show a statistically significant effect. The combination therapy provided the most optimal reduction in pain intensity.   Keywords: Aromatherapy Relaxation, Combination, Hydronephrosis, Slow Stroke Back Massage